2018
DOI: 10.1177/1093526618790747
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoma Subgrouping by Detection of Fusion Transcripts Using NanoString nCounter Technology

Abstract: Background NanoString technology is an innovative barcode-based system that requires less tissue than traditional techniques and can test for multiple fusion transcripts in a single reaction. The objective of this study was to determine the utility of NanoString technology in the detection of sarcoma-specific fusion transcripts in pediatric sarcomas. Design Probe pairs for the most common pediatric sarcoma fusion transcripts were designed for the assay. The NanoString assay was used to test 22 specific fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In conclusion, the NanoString nCounter FusionPlex assay is a screening tool with high sensitivity and specificity [5][6][7]12,13 for the detection of sarcoma-defining fusion gene transcripts in Ewing sarcoma, synovial sarcoma, myxoid liposarcoma, alveolar rhabdomyosarcoma, and desmoplastic small round cell tumors. Its diagnostic yield for rare soft tissue tumors is limited and might require additional or alternative testing.…”
Section: Estimated Diagnostic Coverage Of Nanostring In Stb Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, the NanoString nCounter FusionPlex assay is a screening tool with high sensitivity and specificity [5][6][7]12,13 for the detection of sarcoma-defining fusion gene transcripts in Ewing sarcoma, synovial sarcoma, myxoid liposarcoma, alveolar rhabdomyosarcoma, and desmoplastic small round cell tumors. Its diagnostic yield for rare soft tissue tumors is limited and might require additional or alternative testing.…”
Section: Estimated Diagnostic Coverage Of Nanostring In Stb Tumorsmentioning
confidence: 99%
“…At present, the two novel molecular multiplex methods commonly used in Dutch sarcoma centers are the anchored multiplex PCR (AMP)‐based NGS (Archer FusionPlex Sarcoma assay) and the NanoString nCounter platform . The Archer AMP PCR method targets exons of 26 genes commonly involved in fusion genes of soft tissue tumors, whereas the NanoString assay is a high‐throughput hybridization technique, which uses specific probes that target 174 unique gene fusion junctions in 22 soft tissue tumor types …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGS-based approaches are recommended for classifying small round cell sarcomas where a diagnosis consistent with ES cannot be made following classic immunohistochemistry, FISH, or RT-PCR. Several NGS assays, such as the Archer FusionPlex sarcoma assay, or different NanoString assays are available, but cost is still an issue [36][37][38][39]. Although CD99 is an extremely sensitive marker for ES, CD99 staining is very unspecific as it stains positive in a variety of other tumors [40].…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…There were no false-positive results; nevertheless, four cases were false negative when compared with FISH or RT-PCR. Another NanoString assay for testing 22 fusion transcripts associated with the most prevalent pediatric sarcomas was developed by Javal Sheth et al [25]. The results showed that NanoString assay was 100% concordant with RT-PCR.…”
Section: Improvement In the Diagnosis And Discovery Of New Entities Using Next-generation Techniquesmentioning
confidence: 99%